Recognizing and rewarding employees - Bowen, R. Brayton. (McGraw Hill, 2000)
This is a book about a new frontier-the new workplace. It's a book about the needs and interests of the new workforce-epitomized by the "free agent/employee"-and the tools of recognition and rewards.